2018
DOI: 10.12659/msm.910049
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cpg Island Distribution Between Subgenotypes of the Hepatitis B Virus Genotype

Abstract: BackgroundHepatitis B virus (HBV) genotypes show genomic variations, resulting in different CpG islands in each HBV genotypes or subgenotype. This study aimed to establish reference sequences for each HBV subgenotype of A–H genotypes and to analyze the characteristics of the CpG islands.Material/MethodsThere were 3,037 retrieved whole-genome sequences of HBV genotypes A–H from GenBank, 28 subgenotype reference sequences were established for these genotypes. CpG islands of the subgenotype reference sequences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This variation may be attributed to different mucocutaneous tropisms of various human Papillomavirus genotypes, potentially influencing the CpG island positions within the genome. These findings align with the work of Chen and colleagues, who observed differences in CpG island profiles in hepatitis B virus (7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This variation may be attributed to different mucocutaneous tropisms of various human Papillomavirus genotypes, potentially influencing the CpG island positions within the genome. These findings align with the work of Chen and colleagues, who observed differences in CpG island profiles in hepatitis B virus (7).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, 7 different species of Alphapapillomaviruses were found, which included 5 major and 10 minor Papillomavirus types. A total of 15 viruses had a CpG island; among these genotypes, 46.66% were high-risk (26, 30, 51, 59, 66, 69, 82) and low-risk (6,7,11,32,43,54,91). The vast majority of the CpG islands were identified in the E2 genes in almost 80% of the cases.…”
Section: Profile Of Hpv With a Single Cpg Islandmentioning
confidence: 99%
“…Based on more than 3000 hepatitis B virus (HBV) sequences reported from different countries, our team has divided HBV isolates into 31 different HBV subtypes established by selecting nucleotide with the highest frequency in each position. Using infectious plasmids constructed based on A2, B2, C2, and D1 subtype‐specific reference sequences, in vitro and in vivo studies have confirmed complete biological functions of these reference sequences 21,22 …”
Section: Discussionmentioning
confidence: 86%
“…Using infectious plasmids constructed based on A2, B2, C2, and D1 subtype-specific reference sequences, in vitro and in vivo studies have confirmed complete biological functions of these reference sequences. 21,22 Using the same approaches, in this study, the reference sequence for SARS-CoV-2 was constructed based on genomic sequence of 63 isolated strains. The genome size of the reference strain was 29870 bp.…”
Section: Discussionmentioning
confidence: 99%
“…Viral gene expression is thought to be partially regulated by DNA methylation, which contributes to transcriptional silencing and gene suppression through multiple mechanisms in host tissues (LaMere et al 2019). Several studies found CpG islands in the HBV genomes of different strains, some of which were located at transcription start sites or upstream and downstream of promoters (Vivekanandan et al 2008, Chen et al 2018. In human liver tissues, HBV DNA can be methylated, which plays an important role in the regulation of HBV gene expression (Vivekanandan et al 2008(Vivekanandan et al , 2009.…”
Section: Discussionmentioning
confidence: 99%